Mr. Lincoln's drummer - Wisler, G. Clifton (New York : Lodestar Books, 1995)
A fictional account of the courageous exploits of Willie Johnston, an eleven-year-old Civil War drummer, who became the youngest recipient of the Congressional Medal of Honor.
5.3 (5.0)
AR BOOK
Book Links (A.L.A.)
Elem. School Library Collection
Wilson's Children
6.4
Keywords: Johnston, William J., -- 1850-; Johnston, William J., -- 1850-; Johnston, William J., -- 1850-; Johnston, William J., -- 1850-; Civil War, 1861-1865; History; United States -- History -- Civil War, 1861-1865.; United States; United States -- History -- Civil War, 1861-1865.; United States -- History -- 1861-1865, Civil War; Fiction; Fiction